2016
DOI: 10.1103/physreva.94.052322
|View full text |Cite
|
Sign up to set email alerts
|

Reviving the precision of multiple entangled probes in an open system by simple π -pulse sequences

Abstract: Quantum metrology with entangled states in realistic noisy environments always suffers from decoherence. Therefore, the measurement precision is greatly reduced. Here we applied the dynamical decoupling method to protect the N -qubit quantum metrology protocol and successfully revived the scaling of the measurement precision as N −k with k ∈ [5/6, 11/12]. The degree of the precision revival, as determined by the noise spectrum distribution, indicates that the performance of the protected protocol can be furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…39,40,42 However, a recent study revealed that the memory effects of a non-Markovian environment can be regarded as important physical resources 28,33 to improve QIP in an open quantum system. To further enhance the POS of the RDJA, we utilized the memory effects of the non-Markovian environment, which can be extracted by the DD method 26,39 to mitigate imperfect operations and decoherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40,42 However, a recent study revealed that the memory effects of a non-Markovian environment can be regarded as important physical resources 28,33 to improve QIP in an open quantum system. To further enhance the POS of the RDJA, we utilized the memory effects of the non-Markovian environment, which can be extracted by the DD method 26,39 to mitigate imperfect operations and decoherence.…”
Section: Resultsmentioning
confidence: 99%
“…28 However, because of strong system-environment couplings, structured or finite reservoirs, low temperatures, or large initial system-environment correlations, the dynamics of an open quantum system may deviate substantially from the Born-Markov approximation and follow a non-Markovian process. [28][29][30][31][32] In such a process, the pronounced memory effect, which is the primary feature of a non-Markovian environment, can be used to revive the genuine quantum properties, [28][29][30][31][32][33][34] such as quantum coherence and correlations. Consequently, improving the performance of QIP by utilizing memory effects as important physical resources in the nonMarkovian environment is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperfine interaction with dark spin results in a random local magnetic field δ σ = ∑ A i z i i with a typical linewidth Γ 2 2 * ≈ MHz for NV ensemble as shown in µs) was measured by spin-echo sequence, as shown in Figure 2(d). Because the typical coherent control is much faster than dynamical fluctuations, we take δ as a random time independent variable [5,32]. Furthermore, we assume that NV ensemble dephasing mechanisms are independent and inhomogeneous broadening effect can be described by a Gaussian linetype P (δ) [32].…”
Section: Methodsmentioning
confidence: 99%
“…Solid-state electronic spin defects, including nitrogen vacancy (NV) [1], silicon-vacancy [2] and germaniumvacancy [3] centers in diamond, have garnered increasing relevance for quantum science and modern physics metrology. Especially, NV centers have been systematically studied and employed in interdisciplinary applications facilitated by long electron spin coherence time [4][5][6] at room-temperature. Although, a single NV center can be used for high-spatial-resolution field imaging [7,8], enhancing sensitivity are feasibly achieved by using an ensemble of N NV centers, where the shotnoise limited magnetic field sensitivity can be improved by a factor N [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation